1973
DOI: 10.1080/00103627309366422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature on phosphate sorption isotherms and phosphate desorption

Abstract: Phosphorus sorption isotherms were constructed for two Idaho soils with widely different chemical properties. The soils were equilibrated with various amounts of Ca(H 2 PO 4 ) 2 in 0.01 M CaCl 2 for 1, 3, 7, and 11 days at temperatures of 5°C and 20°C. The two soils which had been equilibrated previously for 11 days at 20°C with various amounts of Ca(H 2 PO 4 ) 2 in 0.01 M CaCl 2 were desorbed at 5°C and 20°C.The rates of sorption and desorption were decreased as the equilibration temperatures were lowered. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…These results mean there was no significant effect of freezing on sorption at 25°C. Gardner and Jones (1973) have reported a similar result, which laboratory studies have shown decreased sorption as temperature is lowered (20 to 5°C). Sorption of P was described by the Langmuir equation.…”
Section: Phosphorus Sorption Behaviorsupporting
confidence: 67%
“…These results mean there was no significant effect of freezing on sorption at 25°C. Gardner and Jones (1973) have reported a similar result, which laboratory studies have shown decreased sorption as temperature is lowered (20 to 5°C). Sorption of P was described by the Langmuir equation.…”
Section: Phosphorus Sorption Behaviorsupporting
confidence: 67%
“…One reason for the different growth responses between the two corps is considered due to the effect of soil temperature on P uptake by plants (Tang et al, 2009). It is found that soil P desorption and consequently availability to plants is greater at higher temperature (Gardner and Jones, 1973;Sánchez and Boll, 2005). As in this rotation system, wheat is grown during cooler months of the year when soil temperature is low, thus P uptake would be low compared to maize, which is grown during warmer months of the year with higher soil temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations: LL, linear-linear; LP, linear-plateau; Exp, Mitscherlich type exponential model temperature on the inorganic P uptake by crop. Winter wheat was grown early in the year when temperature is low, thus P uptake would be low compared to maize, which was grown in later part of year when temperature is high (Gardner and Jones 1973;Sharpley and Ahuja 1982;Sánchez and Boll 2005). When soil Olsen-P level is above the critical value, further P fertilizer application is not justifiable and could increase the amount of P accumulations in soil and losses to water bodies (Heckrath et al 1995;Pote et al 1996;Shepherd and Withers 1999).…”
Section: Discussionmentioning
confidence: 99%